Effects of vaccination timing against respiratory pathogens on performance, antibody response, and health in feedlot cattle. (5th December 2018) - Schumaher, Thiago F; Cooke, Reinaldo F; Brandão, Alice P; Schubach, Kelsey M; de Sousa, Osvaldo A; Bohnert, David W; Marques, Rodrigo S
Abstract: Angus × Hereford calves ( n = 159; 87 heifers and 72 steers) were ranked by sex, BW, and age, and assigned to one of three vaccination schemes against bovine respiratory disease (BRD ): (i) vaccination at weaning (day 0) and revaccination at feedyard arrival (day 30; CON, n = 53), (ii) vaccination 15 d before weaning (day −15) and revaccination 15 d before feedyard arrival (day 15; EARLY, n = 53), and (iii) vaccination 15 d after weaning (day 15) and revaccination 15 d after feedyard arrival (day 45; DELAYED, n = 53). Calves were maintained on pasture from days −15 to 29, transported (day 30) for 480 km to a commercial growing feedyard, and moved (day 180) to an adjacent finishing yard where they remained until slaughter (day 306). Calf BW was recorded on two consecutive days (days −15, −14, 0, 1, 29, 30, 75, 76, 179, and 180), which were averaged for BW gain calculation. Calves were assessed for BRD signs daily from days 0 to 306. Blood samples were collected on days −15, 0, 15, 30, 45, 60, and 75. No treatment effects were detected ( P ≥ 0.49) for BW responses and carcass characteristics ( P ≥ 0.32). Serum titers against bovine viral diarrhea type 1 were greater ( P ≤ 0.05) in EARLY vs. CON and DELAYED from days 15 to 45, and greater ( P < 0.01) in CON vs. DELAYED on days 30 and 45. Serum titers against bovine herpesvirus-1 were greater ( P < 0.01) in EARLY vs. CON and DELAYED on days 0 and 30, and greater ( P < 0.01) in EARLY and CON vs. DELAYED on days 15 and 45. Serum titers against bovine respiratory syncytial virus were greater ( P = 0.05) in EARLY vs. CON on day 0, greater ( P = 0.04) in CON vs. DELAYED on day 15, and greater ( P ≤ 0.03) in EARLY and CON vs. DELAYED from days 30 to 60. Serum titers against parainfluenza3 virus were greater ( P ≤ 0.04) in EARLY vs. DELAYED on days 30 and 45, and greater ( P < 0.01) in CON vs. DELAYED on day 30. Incidence of BRD was less ( P = 0.04) in EARLY vs. CON and DELAYED, and similar (P = 0.99) between CON and DELAYED. Therefore, altering the time of vaccination and revaccination against BRD to provide both doses prior to feedlot entry altered serum antibody responses to BRD pathogens, and alleviated the incidence of this disease in feedlot cattle.